An expanded prescribing role for pharmacists – an Australian perspective - Hoti, Kreshnik; Hughes, Jeff; Sunderland, Bruce (Australasian Medical Journal Pty Ltd, 2011)
Expanded pharmacist prescribing is a new professional practice area for pharmacists. Currently, Australian pharmacists' prescribing role is limited to over-the-counter medications. This review aims to identify Australian studies involving the area of expanded pharmacist prescribing. Australian studies exploring the issues of pharmacist prescribing were identified and considered in the context of its implementation internationally. Australian studies have mainly focused on the attitudes of community and hospital pharmacists towards such an expansion. Studies evaluating the views of Australian consumers and pharmacy clients were also considered. The available Australian literature indicated support from pharmacists and pharmacy clients for an expanded pharmacist prescribing role, with preference for doctors retaining a primary role in diagnosis. Australian pharmacists and pharmacy client's views were also in agreement in terms of other key issues surrounding expanded pharmacist prescribing. These included the nature of an expanded prescribing model, the need for additional training for pharmacists and the potential for pharmacy clients gaining improved medication access, which could be achieved within an expanded role that pharmacists could provide. Current evidence from studies conducted in Australia provides valuable insight to relevant policymakers on the issue of pharmacist prescribing in order to move the agenda of pharmacist prescribing forwards.